2021
DOI: 10.3389/fnins.2021.675732
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions of Circadian Rhythms and Thrombolytic Therapy During Ischemic Stroke Intervention

Abstract: Several endogenous and exogenous factors interact to influence stroke occurrence, in turn contributing to discernable daily distribution patterns in the frequency and severity of cerebrovascular events. Specifically, strokes that occur during the morning tend to be more severe and are associated with elevated diastolic blood pressure, increased hospital stay, and worse outcomes, including mortality, compared to strokes that occur later in the day. Furthermore, disrupted circadian rhythms are linked to higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 191 publications
(225 reference statements)
0
13
0
Order By: Relevance
“…As research progresses and substantial evidence indicates that circadian rhythms govern astrocyte function and injury response, treatment should consider that its molecular targets may be oscillatory and may require different doses at different times of the day. Evidence supports the role of time-of-day changes in the efficacy of rt-PA and hemorrhagic transformation as a potential negative consequence of rt-PA administration (Marler et al, 1989;Liu et al, 2021). Several clinical trials have been attempted and have shown that intravenous thrombolysis with rt-PA between 6:00 a.m. and 6:00 p.m. appears to be less effective and safer, and in patients who start intravenous thrombolysis between noon and midnight, the hemorrhagic transformation rate is lower (Cappellari et al, 2014;Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As research progresses and substantial evidence indicates that circadian rhythms govern astrocyte function and injury response, treatment should consider that its molecular targets may be oscillatory and may require different doses at different times of the day. Evidence supports the role of time-of-day changes in the efficacy of rt-PA and hemorrhagic transformation as a potential negative consequence of rt-PA administration (Marler et al, 1989;Liu et al, 2021). Several clinical trials have been attempted and have shown that intravenous thrombolysis with rt-PA between 6:00 a.m. and 6:00 p.m. appears to be less effective and safer, and in patients who start intravenous thrombolysis between noon and midnight, the hemorrhagic transformation rate is lower (Cappellari et al, 2014;Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 92%
“…Evidence supports the role of time-of-day changes in the efficacy of rt-PA and hemorrhagic transformation as a potential negative consequence of rt-PA administration (Marler et al, 1989;Liu et al, 2021). Several clinical trials have been attempted and have shown that intravenous thrombolysis with rt-PA between 6:00 a.m. and 6:00 p.m. appears to be less effective and safer, and in patients who start intravenous thrombolysis between noon and midnight, the hemorrhagic transformation rate is lower (Cappellari et al, 2014;Liu et al, 2021). Another study found that thrombolysis performed during the day (9:00 a.m. to 9:00 p.m.) had better outcomes compared to nighttime (9:00 p.m. to 9:00 a.m.) (Vilas et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Other treatments (antiplatelet [ 151 ], anticoagulants [ 152 ], thrombolytic drugs [ 153 , 154 ], etc.) might have a greater capacity within the chronotherapy approach, although further investigation is needed [ 47 ].…”
Section: Circadian System and Treatment Developments In Strokementioning
confidence: 99%
“…However, the NINDS rt-PA Stroke Trial ( n = 624) did not find any association between the stroke onset time (and rt-PA treatment given within 3 h of stroke onset) and 3-month outcomes, although there was an association with the occurrence of a symptomatic intracranial hemorrhage within 36 h: patients with stroke onset between 04:01 and 08:00 who received rt-PA had a lower risk of having a symptomatic intracranial hemorrhage [ 13 ]. Some authors explain such an effect by the endogenous circadian rhythm in blood–brain barrier permeability, which shows reduced trafficking during the active phase compared to other periods during the day [ 154 ].…”
Section: Circadian System and Treatment Developments In Strokementioning
confidence: 99%
“…This well-established temporal risk was observed for ischemic and haemorrhage strokes [ 22 , 23 ], although some slight differences were observed in stroke TOAST (Trial of Org 10,172 in Acute Stroke Treatment) subtypes [ 24 ]. The consideration of circadian rhythms may be necessary in order to optimise therapeutic approaches due to the variability of patient response to ischemic stroke and its therapies as well as factors explaining the lack of consistency with the patients’ evolution [ 25 ]. Interestingly, physiological body temperature starts to increase in the morning [ 11 ], coinciding with the period when the peak of stroke has been described [ 22 , 23 , 24 ], and decreases during the sleep period, when the incidence of stroke is lower [ 26 ].…”
Section: Introductionmentioning
confidence: 99%